SEKURITISASI PENANGANAN ISU PENGUNGSI DI SWEDIA: BERHASIL ATAU GAGALKAH? - Tiffany Setyo Pratiwi (UNIDA Gontor, 2018)
This paper will explain about the securitization process in addressing refugees issue in Sweden from 2010 to 2015. This research uses the concept of securitization from Barry Buzan. Some important things which Buzan explained to analyze the process of securitization, such as: Referent Object (Actors), Existential Threats (things or issues that become threats), will proceed to be “Securitizing Move” by “Speech Act”. This paper uses qualitative method which is arranged descriptively with support by secondary data. This paper found that the process of securitization on refugee policies in Sweden from 2010 to 2015 is supported by Sweden Democrats Party and gained the response of Swedish anti-immigrant society, they are conducting the “Speech Act” sustainably. The result is that Sweden’s open policy on refugees has changed by restricting and tightening policy of refugee.